The culture of betel nut chewing and its relationship to chronic energy deficiency (CED) in pregnant women at the Karang Indah Community Health Center - Erma Retnaningtyas; Mifta Huljanna; Hanriska Awidiya Putri; Erni Agit Ekawati (Journal of Midwifery and Nursing, 2026)
Betel nut consumption is closely linked to an increased risk of Chronic Energy Deficiency (CED). The active ingredients in it inhibit the absorption of essential nutrients and can reduce appetite, resulting in inadequate macro and micronutrient intake for mothers. This study aims to determine the relationship between the betel nut culture and the incidence of CED in pregnant women at the Karang Indah Community Health Center. The study design was quantitative and analytical with a cross-sectional approach. A purposive sampling technique was used to select 40 pregnant women from Papua who consume betel nut. Data were collected through a questionnaire to determine the consumption behavior of betel nut and pita lila (lila) to determine whether pregnant women had CED and a lila (lila) <23.5 cm. Data were analyzed using univariate and bivariate methods using the Chi-Square test with an ? value of 0.05. The results showed that the majority of respondents had a habit of consuming betel nut (52.5%), those with CED (45.0%), and those without CED (7.5%). Bivariate analysis showed a significant association between the betel nut culture and the incidence of CED in pregnant women (p = 0.010) with strong relationships. These results indicate that CED is more common in pregnant women who consume betel nut compared to those who do not. Therefore, health education for pregnant women is needed to reduce betel nut consumption.